A Review Article on Spice up the Solution of Inflammation Through Phytomedicines - Mohd. Wasiullah; Piyush Yadav; Amina Ahsan (Emerging Trends in Metabolites, 2024)
Inflammation is a complex, protective immune response essential for healing and combating infection. However, prolonged inflammation is associated with chronic diseases, such as arthritis, cardiovascular disorders, diabetes, and neurodegenerative conditions. Traditional nonsteroidal anti-inflammatory drugs (NSAIDs) and corticosteroids can exhibit adverse effects, particularly with chronic administration. This challenge has encouraged the exploration of natural alternatives. Among various natural anti-inflammatory agents, spices, such as ginger, garlic, turmeric, cardamom, and black pepper have gained significant attention due to their potent bioactive compounds, which have shown promising anti-inflammatory effects. This review discusses the classification, key chemical constituents, historical medicinal uses, and mechanisms of action of these spices, supporting their potential as natural alternatives for inflammation management. Phytomedicines, derived from plants and spices, have garnered significant attention in recent years due to their potent bioactive compounds, which have shown promising anti-inflammatory effects. This comprehensive review focuses on five spices, namely ginger (Zingiber officinale), garlic (Allium sativum), turmeric (Curcuma longa), cardamom (Elettaria cardamomum), and black pepper (Piper nigrum), which have been traditionally used for their medicinal properties.
Keywords: Ginger; anti-inflammatory agents; black Pepper; cardamom; chronic diseases; garlic; inflammation; phytomedicines; spices; turmeric